Caterina in the Big City - Caterina va in città - Paolo Virzi (2005)
When her father, Giancarlo is transferred to Rome from the small country town of Montalto Di Castro, Caterina, a 12 years old girl, will discover her new classmates, a totally new world, an ambient extremely divided politically. She starts developing her friendship with the "left side", represented by Margherita, and the right, Daniela, side of her class. She will lose herself, without knowing who she really is. However, maybe Edward, the young Australian boy, who lives in the apartment across hers, can help her more that she thinks.
Keywords: Comedy, Drama